Avifaunal Diversity in Managed Urban Ecosystem: A Case Study of Banaras Hindu University, Varanasi - Singh, Rinku; Tiwari, Amit Kumar; Kumar, Sudhanshu; Singh, Gopal Shankar (Ecological Questions, 2024)
University campuses are becoming important places for conducting a large number of studies on plant and animal taxa including avian diversity. However, a systematic study on the avian diversity in the Banaras Hindu University (BHU) campus (Asia’s largest residential university campus) of Varanasi is still lacking. The present study deals with the species abundance, diversity and species richness of avian communities in the BHU campus. We conducted a bird survey in the BHU campus between 2019 and 2020. Employing line-transect method, a total of 141 bird species under 62 families were recorded from the study area. A rich diversity of species recorded indicates the importance of the university campuses in urbanized region to serve as a critical habitat for birds. To conserve this rich bird diversity of the campus, we suggest sustainable management of habitats through restoration of degraded habitats, reduction in habitat destruction, conservation awareness programmes and increased research on assessment of diversity.